Comparative Effectiveness of a Magnesium Combination Versus Magnesium Oxide for Leg Cramps in Pregnancy: An Observational Study - Murat Polat; Sait Erbey; Ömer Osman Eroğlu; Aysu Yeşim Tezcan; Çağanay Soysal (Women’s Health and Multidisciplinary Research, 2026)
Background and Aim: To compare magnesium oxide with a magnesium citrate–glycinate–malate combination in terms of the frequency, duration, and intensity of pregnancy-related leg cramps. Materials and Methods: This single-center, retrospective, observational comparative study evaluated 124 women with singleton pregnancies in the third trimester (62 combination, 62 oxide) who had used a magnesium supplement for at least four weeks. The combination group received 200 mg of elemental magnesium daily, whereas the oxide group received 365 mg daily. The groups were not randomized but were formed according to the type of magnesium supplement each participant had previously used. Weekly cramp frequency, duration (seconds), and intensity (0–10 visual analog scale) were recorded before and one month after the initiation of therapy. Between-group comparisons were performed using Student’s t-test or the Mann–Whitney U test, within-group comparisons using the paired t-test or Wilcoxon test, and comparisons of categorical variables using the chi-square test. Results: The groups were comparable at baseline (all p>0.05). In both groups, all three parameters decreased significantly after treatment (all p